Estudio de factibilidad para la creación de una empresa proveedora de una bolsa o funda económica de víveres, cantón Quevedo, año 2015 - Chagcha Tiglla, Walter Oswaldo (2016)
The business activity is to conduct the sale of consumer products and packaged specifically food and vegetables, in a personalized way, of door to door, directly from the company to the end consumer, for this you must create a company that under the guidelines of Good Living offers high quality products mainly watching their presentation and hygiene thus able to satisfy the tastes and demands of consumers, routing thus meeting the objectives. The main objective of this company is to provide the quevedeña citizenship especially to the San Camilo fresh produce sector through direct sales and is detected through research conducted in the field indicated no company ever devoted to this work, for which the company implemented a system of door-to-door distribution, ie a personalized sales strategy with the main promotions and sometimes specify a percentage discount without affecting the profitability of the company. Based on this perspective vision it is to get in a short-term competitiveness and positioning in terms of the distribution of food and vegetables in the form door to door, so as to achieve sustained and sustainable business growth maintaining a high percentage of participation in the local market. By the company and certain studies made an investment of $ 40,000 for the implementation of the business in question taking into account all details concerning health, safety, accessibility, quality, presentation, etc. For all detailed the company recommends providing fresh, nutritious products to meet the stringent quality standards, ensuring our customers trust and confidence with our products and seeking to maintain loyalty to our products through excellent customer service, demonstrating our commitment to community.